2016
DOI: 10.1596/1813-9450-7806
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainty as a Factor in Investment Decisions: The Case of the Russian Federation's Regions

Abstract: The Policy Research Working Paper Series disseminates the findings of work in progress to encourage the exchange of ideas about development issues. An objective of the series is to get the findings out quickly, even if the presentations are less than fully polished. The papers carry the names of the authors and should be cited accordingly. The findings, interpretations, and conclusions expressed in this paper are entirely those of the authors. They do not necessarily represent the views of the International Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…The survey was conducted by the HSE University in 2014 and contains information about 1,950 rms from 60 Russian regions. 3 The same survey was used by (Levina et al, 2016) Did your rm receive any nancial support from federal, regional, and municipal government in 20122013? (Give one answer in each row) .…”
Section: Data Descriptionmentioning
confidence: 99%
“…The survey was conducted by the HSE University in 2014 and contains information about 1,950 rms from 60 Russian regions. 3 The same survey was used by (Levina et al, 2016) Did your rm receive any nancial support from federal, regional, and municipal government in 20122013? (Give one answer in each row) .…”
Section: Data Descriptionmentioning
confidence: 99%
“…Recent research into entrepreneurial orientation and investment decisions of Russian SMEs found that operating in unstable institutional environment characterised by a large 'shadow economy' compels many companies to make decisions based on the information obtained from informal, sometimes, illegal contacts they develop with the local officials in order to circumvent the limitations imposed by formal rules and regulations (Wales et al, 2016). Unfortunately, large inconsistencies in informal relations combined with instability in the protection of private property rights leave many Russian companies exposed to private raiding, creating fundamental threats to their existence (Levina et al, 2016).…”
Section: Theory and Research Questionsmentioning
confidence: 99%